RETROSPECTIVE STUDY OF MAXILLARY CANINES IMPACTED PROFILES AT DENTAL HOSPITAL OF FACULTY OF DENTISTRY PADJADJARAN UNIVERSITY - Ginda Adilla Suwandi; Indra Hadikrishna; Farah Asnely Putri; Yurika Lita (Faculty of Dentistry, Universitas Islam Sultan Agung, 2022)
Background: The maxillary canine have a key role in the aesthetics and continuity of the dental arch. Impacted canines are the most frequently impacted teeth apart from the third molars of both the maxilla and mandible. The purpose of this study was to determine and obtain a description of the impact profile of maxillary canines at RSGM UNPAD based on age, sex, classification, type of treatment action plan.Method: This research was a retrospective descriptive study conducted from February to March 2021 based on inclusion and exclusion criteria. The research sample was taken using purposive sampling technique and determination of the impacted image using a classification based on Stivaros Mandal, Ghenoima, and Yamammoto, analyzed with ImageJ software by interobserver and intraobserver. and tested using Kappa statistics for reliability.Result: There were 76 patients who had cases of maxillary canine impaction with an age prevalence range of 10-25 years and the majority occurred in women (42.56%) and men (15.20%). Analysis of the Stivaros and Mandall classification of 59.40% grade III canine impacted patients, the greatest prevalence of the Ghenoima classification in Type E 27.00% and the Yamammoto classification of the largest prevalence in Type II 41.40%. The results of the analysis of the action plan for the treatment of patients with exposure surgery had a percentage of 0.03% and Odontectomy 0.03%.Conclusion: The majority of maxillary canine impacted prevalence occurred at the age of 10-25 years with grade III angulation, mesio-angular position between the anterior-inferior maxillary sinus.